Nós estamos igual kapràn : um estudo da Terra Indígena Mãe Maria no contexto dos neoaldeamentos - Ribamar Ribeiro Junior (2020)
This work deals with the neo-village process of the “Gavião” people in the Mãe Maria Indigenous Land, in the municipality of Bom Jesus do Tocantins, PA. The more general objective is to understand the processes of formation of new villages from the splits/mergers before the displacement to the Indigenous Territory Mãe Maria (ITMM) and the contemporary dissolution of the “Parkatêjê community”. Therefore, I present ethnographic data that bring elements to understand the current situation of reorganization of the “Gavião” people. More specifically, from the "neo-village" category, I try to understand: i) the previous situation of the compulsory displacement of this people to ITMM, in a perspective compared to other Jê-Timbira people, who differentiated themselves through the fission/split pendulum; ii) the new-village movement as a form of differentiation that occurred between 2001 and 2009; iii) the divisions that have been taking place at ITMM since 2012, differentiating them from other types of fragmentation that marked the trajectory of the “Gavião” before this date.